1991
DOI: 10.1002/mrd.1080300412
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of filamentous actin in and around spermatids and in spermatozoa of Australian conilurine rodents

Abstract: The distribution of filamentous actin around the maturing sperm head and in spermatozoa of four species of Australian conilurine rodents was investigated at the light and electron microscopic levels. Similar results were obtained for all the species studied. Mechanically isolated spermatids had NBD-phallacidin-positive longitudinal bands of fluorescence over the dorsolateral surface and, in late spermatids, bands of bright fluorescence passed perpendicularly from the dorsal convex to ventral concave surface. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 35 publications
3
23
0
Order By: Relevance
“…So far, only nonfilamentous actin has been detected in the neck of mammalian sperm, including rat and mouse (Flaherty et al, 1983(Flaherty et al, , 1986(Flaherty et al, , 1988Virtanen et al, 1984;Welch and O'Rand, 1985;Breed and Leigh, 1991;Yagi and Paranko, 1992;Vogl et al, 1993). The present immunogold labeling results confirm the earlier reports localizing actin into the amorphous material on the neck region of human, bovine, and hamster spermatozoa (Flaherty et al, 1988).…”
Section: Necksupporting
confidence: 94%
See 2 more Smart Citations
“…So far, only nonfilamentous actin has been detected in the neck of mammalian sperm, including rat and mouse (Flaherty et al, 1983(Flaherty et al, , 1986(Flaherty et al, , 1988Virtanen et al, 1984;Welch and O'Rand, 1985;Breed and Leigh, 1991;Yagi and Paranko, 1992;Vogl et al, 1993). The present immunogold labeling results confirm the earlier reports localizing actin into the amorphous material on the neck region of human, bovine, and hamster spermatozoa (Flaherty et al, 1988).…”
Section: Necksupporting
confidence: 94%
“…Solubility of tail actin in SDS is supportive for its unpolymerized nature and agrees with the negative results obtained with fluorescent phallotoxins (Flaherty et al, 1983(Flaherty et al, , 1986Virtanen et al, 1984;Welch and O'Rand, 1985;Breed and Leigh, 1991;Yagi and Paranko, 1992;Vogl et al, 1993). Due to the crossreactivity of N350 antibody in the rat and mouse sperm tail and because of the different properties of solubility, the putative mutual associations between actin and 53 kDa polypeptide remained undetermined.…”
Section: Tailsupporting
confidence: 81%
See 1 more Smart Citation
“…Transmission electron microscopy (TEM) of the sperm head of laboratory rats (Rattus norvegicus) and mice (Mus musculus) has since shown that this sperm head morphotype has a highly complex structural organization, with the apical hook containing a nuclear extension, extensive development of the subacrosomal space rostrally as a perforatorium, and a complex asymmetrical acrosome (Piko, 1969;Lalli and Clermont, 1981;Oko and Clermont, 1988). A further morphological elaboration of the sperm head occurs in most species of Australian hydromyine rodents where two additional extensions, largely made up of cytoskeletal material, project from the upper concave surface (Breed, 1984(Breed, , 1997Flaherty and Breed, 1983;Breed and Leigh, 1991;.…”
mentioning
confidence: 97%
“…These processes develop late in spermiogenesis and are largely composed of electron-dense material that is continuous with the perforatorium in the apical hook [15][16][17][18][19][20]. The chemical composition of these processes is largely unknown although filamentous actin has been shown to be present [17,18,[20][21][22] that is not present in the perforatorium of the mature sperm head of the laboratory rat [9,23,24]. The objective of the present study was to isolate the ventral processes (VPs) and determine their protein composition by SDS-PAGE and Western blotting, and by TEM after immunogold labeling with the use of antisera raised against proteins of the perforatorium in the laboratory rat and of the perinuclear theca in the bull.…”
Section: Introductionmentioning
confidence: 97%